Herbal Remedies Effective on Treating Idiopathic Pulmonary Fibrosis - Aditi Chaudhary; Somesh Shukla; Ravi Kumar; Hema Barti (Research Center for Rational Use of Drugs (RCRUD), 2023)
Through a multi-level and multi-target treatment approach, herbal medicines, such as Traditional Chinese Medicine (TCM), have been identified as revolutionary medical treatment for IPF. Due to their natural properties, herbal medicines have shown to possess low adverse effects, stable therapeutic impact, and no obvious drug dependencies. Herbal medicines have also shown anti-inflammatory and anti-fibrotic effects, which make them a promising therapeutic target for IPF. A growing number of formulas, herbal components, and various forms of Chinese herbal medicine extracts are available for IPF patients in China. This review summaries the role of herbal medicines in the prevention and treatment of IPF.